Case Report: Long-term surgical outcomes in pug dogs with articular facet dysplasia-associated thoracolumbar myelopathies - Tauro, Anna; Driver, Colin J.; Rose, Jeremy; Fernandes, Ricardo; Rusbridge, Clare (Frontiers in Veterinary Science, 2025)
Pug dogs are predisposed to thoracolumbar myelopathy associated with vertebral articular process dysplasia, suggesting a biomechanical etiology. While surgery is commonly pursued, long-term outcomes remain poorly defined. This retrospective descriptive case series reports on seven Pug dogs that underwent surgical treatment for thoracolumbar myelopathy and were followed up for at least 7 years postoperatively. All dogs were part of a previously published cohort treated at the same institution and were included in this follow-up based on caregiver consent. Dogs were classified into three groups—intervertebral disc protrusion (IVDP), spinal arachnoid diverticulum (SAD), or pia-arachnoid fibrosis (PAF)—based on imaging and intraoperative findings. All dogs underwent vertebral stabilization, with decompression performed in the IVDP and SAD groups. Follow-up data were collected via caregiver questionnaire and review of clinical records. Temporary clinical improvement or stabilization was achieved in five of seven Pug dogs (71%), particularly in the IVDP and SAD groups. Recurrence of neurological signs was noted in four of these five dogs (80%), with a median time to recurrence of 8.9 months. The median survival time following surgery across all seven dogs was 3.2 years. Dogs with PAF demonstrated the poorest outcomes. Favorable outcomes were associated with younger age, shorter lesion extension, and milder T2-weighted hyperintensity. Urinary and/or fecal incontinence and recurrent urinary tract infections were common comorbidities. Surgery was considered beneficial by caregivers in four (57%) of seven cases. In conclusion, vertebral stabilization with decompression may provide temporary clinical benefit in Pug dogs with thoracolumbar myelopathy. However, recurrence is common, and PAF may predict a less favorable prognosis. Larger-scale studies are warranted to explore potential associations between intrathecal inflammation, the necrotizing meningoencephalitis (NME) risk haplotype, and response to adjunctive therapies such as corticosteroids or cerebrospinal fluid diversion techniques. Urinary incontinence should be closely monitored to minimize complications.